Evaluation of an electronic sky derotation scheme for a phased array fed reflector antenna - Young, A.; Warnick, K.; Davidson, David (2014)
© 2014 European Association on Antennas and Propagation. In recent years a number of reflector antenna radio telescopes have been fitted with Phased Array Feeds (PAF) [1], [2], [3], [4] as part of ongoing research on the development as well as the effective use of this technology. The baseline design for SKA phase 1 also specifies the use of this technology in the SKA-survey instrument [5]. One major advantage of using a PAF is that it significantly improves the survey speed due to an increase in the Field-of-View (FoV) as multiple beams on the sky may be formed simultaneously. In addition to this, the beamforming capability of such systems also offer the advantage of being able to optimize various Figures-of-Merit (FoM). This ability is often utilized to improve the stability of the beam response over the FoV in order to improve imaging dynamic range [6], [7], [8].